A New Controlled-Release Material Containing Metronidazole and Doxycycline for the Treatment of Periodontal and Peri-Implant Diseases: Formulation and In Vitro Testing - Livia Nastri; Alfredo De Rosa; Vincenza De Gregorio; Vincenzo Grassia; Giovanna Donnarumma (Hindawi Limited, 2019)
Background. Several locally administered antimicrobials have been studied in the literature as adjunctive or primary treatments for periodontitis and peri-implantitis with conflicting results. Objective. The aim of this study was twofold: (1) the formulation of a controlled-release material containing metronidazole and doxycycline; (2) an in vitro evaluation of its antibacterial properties against planktonic and biofilm species involved in periodontal and peri-implant diseases. Methods. Doxycycline (10 mg/ml) and metronidazole (20 mg/ml) were incorporated into a hydroxyethylcellulose-polyvinylpyrrolidone-calcium polycarbophil gel. Three milliliters of gel were dialyzed against Dulbecco's phosphate-buffered saline for 13 days. Antibiotics release at 3, 7, 10, and 13 days was determined spectroscopically. The inhibitory activity of the experimental gel was tested against A. actinomycetemcomitans, S. sanguinis, P. micra, and E. corrodens with an agar diffusion test, an inactivation biofilm test, and a confocal laser scanning microscope study (CLSMS) for S. sanguinis up to 20 days. Results. After 13 days, the released doxycycline was 9.7% (at 3 days = 1.2 mg; 7 days = 0.67 mg; 10 days = 0.76 mg; 13 days = 0.29 mg), while metronidazole was 67% (30 mg, 6.8 mg, 2.5 mg, and 0.9 mg at the same intervals). The agar diffusion test highlights that the formulated gel was active against tested microorganisms up to 312 h. Quantitative analysis of biofilm formation for all strains and CLSMS for S. sanguinis showed a high growth reduction up to 13 days. Conclusions. The in vitro efficacy of the newly formulated gel was confirmed both on planktonic species and on bacterial biofilm over a period of 13 days. The controlled-release gel containing metronidazole and doxycycline had an optimal final viscosity and mucoadhesive properties. It can be argued that its employment could be useful for the treatment of periodontal and peri-implant diseases, where conventional therapy seems not successful.